Ca(II)‐Catalyzed Regioselective Cascade Synthesis of Oxindolyl‐ Naphthofurans through Meyer‐Schuster type Rearrangement. Issue 21 (27th December 2016) - Yaragorla, Srinivasarao; Dada, Ravikrishna; Singh, Garima; Pareek, Abhishek; Rana, Monika; Sharma, Anuj K.
Abstract: Highly regioselective synthesis of 3‐Oxindolyl naphthofurans has been described through an interesting Meyer‐Schuster (M−S) type rearrangement followed by oxacyclisation using environmentally benign calcium salt. This synthetic protocol is ornamented with many of the green synthetic aspects such as solvent free, one pot cascade, ‐atom economy, step economy and the use of calcium salt which is highly abundant in the nature. The selected compounds were tested for their preliminary anti‐amyloidogenic properties to highlight the importance of such compounds and methodologies. Abstract : Highly regioselective synthesis of 3‐Oxindolyl naphthofurans has been described through an interesting Meyer‐Schuster type rearrangement followed by oxacyclisation using environmentally benign Calcium salt. This synthetic protocol ornamented with many of the green chemistry principles such as solvent free, one pot cascade, atom economy, step economy and the use of Calcium salt which is highly abundant in the nature. The selected compounds were tested for their preliminary anti‐amyloidogenic properties to highlight the importance of such compounds and methodologies.